INCLUSIVE DEVELOPMENT MODELS: STRATEGIES TO REDUCE INCOME GAPS AND SUPPORT SUSTAINABLE ECONOMIC GROWTH - Silvia Ekasari; Loso Judijanto (CV. Adiba Aisha Amira, 2025)
The inclusive development model is a strategic approach that aims to reduce income inequality and support sustainable economic growth. It prioritises the principles of equity in resource distribution, access to basic services such as education, health and infrastructure, and ensures the active participation of all segments of society, including vulnerable groups. Through income redistribution policies, quality job creation, and collaboration between the public and private sectors, inclusive development has the potential to address structural issues such as poverty, unemployment, and social inequality. With a holistic approach, this model not only promotes quantitative economic growth, but also builds the foundation for a fair, resilient and sustainable economy in the long run.